Pelatihan Peningkatan Mutu Penelitian Tindakan Kelas Guru SMP Kecamatan Tualang Kabupaten Siak - Isjoni Isjoni; M. Yogi Riyantama Isjoni; Riki Apriyandi Putra (Journal of Community Engagement Research for Sustainability, 2021)
The purpose of this devotion is to provide understanding and experience about the writing of PTK to teachers of SMPN Tualang District siak. It is expected that with this devotion all junior high school teachers can carry out the writing of PTK as a scientific work of teachers later. The target of this devotion is teachers who are constrained by his promotion because of the absence of research as his scientific work. It is concluded that, there are still many teachers who do not understand the nature of this Class Action Research (PTK). This is because generally teachers are not used to writing PTK, even when teachers who have followed PLPG are indeed given PTK materials, but the allocation provided does not allow them to be able to master about PTK. One of the things that can be done by teachers is to imitate the PTK report that has been made by previous teachers. So impressed just coffee paste.  The enthusiasm of Tualang Junior High School teachers in participating in the devotional activities is quite high, question after question presented to the source is quite active and subject to the targets of the PTK itself. At the initial and to-end activities for 4 days (32 hours) most of them understand and the motivation to produce the product is quite high. When the implementation of legiatan there is no understanding, and the earnestness of irtu is seen from time to time in both the discussion of the group and the classic.   At the end of the devotional activities, each teacher is required to prepare a product in the form of a proposal or a complete report of PTK. The availability of the program until the last day only produces 5 PTK products that will be analyzed